The Evolution of the Vibraphone in the Development of Musical Styles - Šinkūnas, Marius (Jaunųjų mokslininkų darbai, 2022)
The paper analyses the evolution of the vibraphone in the development of musical styles. The vibraphone is recently built instrument in comparison to other percussion instruments. Its original version was built just over 100 years ago – in 1916. Although the evolution of the vibraphone is not a new subject of research in foreign literature, it is usually examined in the context of jazz performers. There are fewer works that discuss the evolution of the vibraphone in the development of various musical styles, and there are none that mention the Baltic countries, specifically Lithuania. During the research, the methods of analysis, synthesis and generalization of scientific literature and repertoires were used.The analysis of scientific literature showed that since 1921, when the vibraphone was presented at the World Instrument Exhibition in the United States, the performance style of this musical instrument has changed significantly, both in terms of timbre and technique. In the modern world of music, the vibraphone is used not only for melodic lines, but also for accompaniment, counterpoint, rhythm and harmony, damping, sound suppression and complex pedaling. This is a modern school of vibraphone performance. Unfortunately, due to historical and political circumstances in Lithuania, the vibraphone has not become a part of the music culture and is still considered a niche instrument.
Keywords: vibraphone; evolution; musical styles; school of vibraphone performance